Ritual Perang Topat dan Harmoni Lintas Agama dalam Sejarah Budaya Lombok Barat - Dewi Puspita Ningsih; Baiq Mulianah; Galih Suryadmaja; Lalu Rohadi Rahman; Ahmad Fauzan; Ahmad Dirgahayu Hidayat (CV. Global Cendekia Inti, 2026)
This article examines the Perang Topat ritual as a cultural-historical practice representing interreligious harmony in West Lombok, a region where Sasak and Balinese communities have long interacted, forming a distinctive socio-religious configuration. Held in Lingsar, the ritual functions not only as a religious tradition but also as a cultural mechanism for managing differences in identity, social tensions, and shared interests related to vital water resources. The study focuses on the historical context, ritual structure, symbolic meanings, and social functions of Perang Topat in sustaining intercommunal harmony. Employing a qualitative approach grounded in ethnography and cultural history, data were collected through participant observation, in-depth interviews, and documentation studies. The findings reveal that the ritual serves as a space for symbolic communication, social integration, and conflict management between Hindu and Wetu Telu Islam communities. Perang Topat demonstrates that harmony is a product of socio-historical negotiation and remains relevant as a living cultural heritage for strengthening social cohesion in Indonesia’s multicultural society.